Perinatal outcomes in 375 children born after oocyte donation: a Danish national cohort study - Malchau, Sara S; Loft, Anne; Larsen, Elisabeth C; Aaris Henningsen, Anna-Karina; Rasmussen, Steen; Andersen, Anders Nyboe; Pinborg, Anja (Fertility and sterility, 2013)
To describe perinatal outcomes in children born after oocyte donation (OD) compared with in vitro fertilization (IVF), intracytoplasmic sperm injection (ICSI), and spontaneous conception (SC). National cohort study. Fertility clinics. Three hundred seventy-five children born after OD during the period 1995-2010. None. Mean birth weight, mean gestational age, risks of low birth weight (LBW), preterm birth (PTB), congenital malformations, cesarean delivery, preeclampsia, and admittance to neonatal intensive care unit. We found an increased risk of PTB in OD pregnancies. The adjusted odds ratio (AOR) of PTB in OD singletons was 1.8 (95% CI, 1.2-2.69), 2.5 (95% CI, 1.7-3.6), and 3.4 (95% CI, 2.3-4.9) compared with IVF, ICSI, and SC, respectively. The risk of LBW was also increased. The AOR of LBW was 1.4 (95% CI, 0.9-2.2), 1.8 (95% CI, 1.2-2.8), and 2.6 (95% CI, 1.7-4.0) compared with IVF, ICSI, and SC. The risk of preeclampsia was increased in OD pregnancies with an AOR of 2.9 (95% CI, 1.8-4.6), 2.8 (95% CI, 1.7-4.5), and 3.1 (95% CI, 1.9-4.9) compared with IVF, ICSI, and SC. After additional adjustment for preeclampsia, perinatal outcome improved. Among the twins, the difference between the groups was less pronounced. Pregnancies after OD have a poorer perinatal outcome than those after standard IVF and ICSI mainly because of the high prevalence of preeclampsia.